Articulated coordination of the right arm underlies control of bow parameters and quick bow reversals in skilled cello bowing - Verrel, Julius; Woollacott, Marjorie; Lindenberger, Ulman (Frontiers in Psychology, 2014)
Stringed instrument bowing is a complex coordinative motor skill acquired though years of intense practice. We apply a novel “freezing” analysis to investigate how movement at different joints contributes to bow transport (movement amplitude), stabilization of bow parameters (angle, velocity) during bow movements, and quick reversals of bow direction (acceleration amplitude). Participants were ten advanced or professional cellists (19-32 years, at least 10 years of practice) and ten age-matched novice players. Arm and bow movements were recorded using 3D motion capture. To assess how performance depends on articulated use of the right arm, actual data were compared to surrogate data, generated by artificially removing movement at (“freezing”) individual joints in measured arm movements. This analysis showed that both elbow and shoulder significantly contribute to bow transport in experts, while only the shoulder contributed to bow transport in novices. Moreover, experts showed more strongly increased variability of bow parameters and reduced acceleration amplitudes at bow reversals for surrogate compared to actual movement data. This indicates that movement across joints was organized to reduce bow variability and achieve quick bow reversals. Corresponding effects were less pronounced or absent in the novices, in particular for the wrist and elbow. Our results demonstrate the importance of articulated use of the right arm and clarify the contribution of different joints in experts’ bowing performance. Moreover, they support theories of motor control and learning that propose exploitation of biomechanical degrees of freedom, in particular of distal joints, as a critical component in skilled motor performance.